THE CURRENT STATE AND DIRECTIONS OF THE DEVELOPMENT OF HIGHER EDUCATION IN THE PRC - Pyrozhenko, Lidiia; Smolinchuk, Larysa (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article analyzes the peculiarities of the formation of higher education in the People's Republic of China, its current state and the main strategies for the development of Chinese universities until 2035. The implementation of state education reform projects at the end of the 20th and the beginning of the 21st century brought a number of Chinese universities to leading positions in the world, turning China into a country with the world's largest higher education. Study Conduct. To achieve the objectives of the research, the methods of comparative analysis and theoretical generalization of approaches in educational science and practice were used. Results. Тhe implementation of state education reform projects in the early 20th and early 21st centuries brought a number of Chinese universities to leading positions in the world, turned China into a country with the largest higher education in the world. The construction of a system of educational institutions of different levels is aimed at ensuring equal and fair access of the population to higher education, as well as the needs of the country's economy in highly qualified, innovative personnel that are constantly growing and developing. Conclusions. According to the strategy of intensive development of higher education, China plans to form an extensive system of high-quality and accessible higher education by 2035, to achieve the overall power and influence of Chinese education on the international arena, and to increase the competitiveness of higher education in the context of the country's transformation into a world educational power